PANDANGAN HUKUM PIDANA ISLAM MENGENAI KEKERASAN FISIK TERHADAP ANAK - Hidayat, Taufik (Faculty of Shariah of State Institute for Islamic Studies Batusangkar, Indonesia, 2016)
In order to provide solutions concerning with physical abuses toward children, Indonesia has issued special regulation, namely UU No. 35 tahun 2014 about Perubahan (amendment) UU No. 23 Tahun 2002 about Child Protection. In line with this regulation, a study was carried out to figure out perspectives of Islamic civil law toward children’s physical abuses. This study belonged to normative yuridis through library study and employing yuridis normative analysis technique. The study showed that prohibitions against children’s physical abuses were supported by the second Islamic civil law, namely hifzhan-nafs. However, using physical punishments are tolerated for reasons which have pointed out by the law. In addition, death penalty, imprison, and fine payment are similar to Islamic civil law with minor differences in implementation.